2020
DOI: 10.36366/frontiers.v32i3.583
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Global Mindedness in Short-Term Community-Based Global Learning Programs: The Importance of Strategic Design, Collaboration, and Reflection

Abstract: Trends toward short-term academic service-learning abroad necessitate programs designed to maximize effectiveness and measurement of outcomes. The current study sought to strategically foster and measure increases in global mindedness during an immersive community-based global learning program abroad. University students studying either Computer Science or Spanish collaborated to design curriculum and host a technology summer camp for junior-high students in the Dominican Republic. The semester before the two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The 396 US undergraduate students who participated in Hett's (1993) original GMS research demonstrated lower ethnocentric behavior, higher cultural awareness, and a greater sense of interconnectedness with culturally different others. In an STSA program in the Dominican Republic involving immersive communitybased global learning that emphasized extensive pre-departure collaboration with the host community and critical reflection, 48 American university students increased their GMS scores in a pre/post measurement design (Matheus & Gaugler, 2020). Longer terms abroad (defined as one semester or more) were found to increase GMS scores compared to STSA results in a large-scale study involving 520 university participants in the US (Kehl & Morris, 2008).…”
mentioning
confidence: 90%
“…The 396 US undergraduate students who participated in Hett's (1993) original GMS research demonstrated lower ethnocentric behavior, higher cultural awareness, and a greater sense of interconnectedness with culturally different others. In an STSA program in the Dominican Republic involving immersive communitybased global learning that emphasized extensive pre-departure collaboration with the host community and critical reflection, 48 American university students increased their GMS scores in a pre/post measurement design (Matheus & Gaugler, 2020). Longer terms abroad (defined as one semester or more) were found to increase GMS scores compared to STSA results in a large-scale study involving 520 university participants in the US (Kehl & Morris, 2008).…”
mentioning
confidence: 90%